How the Bible came to us - Doney, Meryl, 1942; Dennis, Peter, 1950- (Tring [Hertfordshire] ; Belleville [Mich.] : Lion Pub., 1985)
Discusses how the Bible came into being, who wrote it, early and modern translations, monks and manuscripts, and the importance of the Bible.
Cover has subtitle: the story of the book that changed the world.
"A Lion book."
Includes index.
Keywords: Bible -- History -- Juvenile literature; Bible -- Versions -- Juvenile literature; Bible -- Publication and distribution -- Juvenile literature; Bible